Effect of time of paclobutrazol application on growth, quality and yield of potato (solanum tuberosum l.) in the Lowveld of Zimbabwe - Simeti, Hillary (Midlands State University, 2017)
Irish potato is a cool season crop which require low temperatures for high yields. In potato production tuberisation is an important and complex process. High temperatures reduce successful cultivation of potato in the lowveld of Zimbabwe because they tend to promote vegetative growth at the expense of tuber production. High temperatures may increase in gubberellin activity that inhibits tuberisation.To overcome this problem paclobutrazol can be used to overcome the inhibitory effect caused by gibberellins. The effect of paclobutrazol was tested under field conditions. An experiment was set up at Chiredzi Research Station to investigate the effect of paclobutrazol on growth, yield and quality of potatoes. A total of eight treatments were used for this experiment ,which were replicated three times in a Complete Randomised Design to investigate the effect of time of paclobutrazol application on the growth, yield and quality of potato. Paclobutrazol was applied at 28 DAP, 35DAP, 42DAP,49DAP,56DAP,63DAP,70DAP and 77DAP. Early application of paclobutrazol at 28DAP and35 DAP increased potato stem diameter and diameter of tubers compared to late application of paclobutrazol. Early application of paclobutrazol at 28 DAP and 35 DAP reduced the number of tubers ,reduced sugar content ,potato stem length compared to late application of paclobutrazol.